Strategi Kepemimpinan Kyai dalam Pembentukan Karakter Wirausaha Santri Melalui Pemanfaatan Bioflok di Pondok Pesantren Babakan Jamanis - Nisa Nurrohmah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
This research aims to describe the leadership strategies of kyai in forming the entrepreneurial character of santri through the use of biofloc at the Babangan Jamanis Islamic boarding school. The subjects in this research were the caretakers of the Babangan Jamanis Islamic boarding school, biofloc entrepreneurship coaches and students who were involved in forming entrepreneurial character in the Islamic boarding school through the use of Biofloc. The data collection techniques used by researchers are observation, interviews and documentation techniques. The data analysis technique in this research involves data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Kyai's leadership strategy in forming the entrepreneurial character of students through the use of biofloc at the Babakan Jamanis Islamic Boarding School uses Geoff Mulgan's theory which includes goals, environment, direction, action and learning. This biofloc is one of the entrepreneurial programs supported by the government to develop entrepreneurship in Islamic boarding schools. The presence of biofloc in the Babakan Jamanis Islamic Boarding School environment supports the formation of the entrepreneurial character of students. The facilities provided and collaboration with fisheries experts create a conducive environment for the development of entrepreneurial skills. Kyai directs the students to undertake training to understand and learn how to manage fish with the biofloc system. In this effort, students are guided by trainers who are very experienced in the biofloc system from the Provincial Agriculture and Fisheries Service. The actions taken by Kyai and students in managing the biofloc business reflect commitment and hard work in achieving entrepreneurial goals. In his learning activities, Kyai selects several students who are believed to have an interest and talent in fish management to take part in training. The results of the formation of the entrepreneurial character of students through the use of biofloc show that students can be said to have an entrepreneurial character. Students have a self-confident character, are task and result oriented, dare to take risks, have leadership, are forward-looking and original.